2018
DOI: 10.1186/s12891-018-2274-5
|View full text |Cite
|
Sign up to set email alerts
|

Patients with severe low back pain exhibit a low level of physical activity before lumbar fusion surgery: a cross-sectional study

Abstract: BackgroundPeople with severe low back pain are at higher risk of poor health. Patients scheduled for lumbar fusion surgery are assumed to have low levels of physical activity, but few data exist. The aim of the study was firstly to investigate preoperative levels of objectively measured physical activity in patients with severe low back pain waiting for lumbar fusion surgery, and secondly to investigate whether factors in the fear-avoidance model were associated with these levels.MethodsWe included 118 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Low physical activity is a global health problem and may add a greater risk for a poor surgical outcome for patients undergoing LSF [ 5 ]. A cross-sectional study found that 83% of patients scheduled for LSF did not adhere to the World Health Organization recommendations regarding physical activity, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low physical activity is a global health problem and may add a greater risk for a poor surgical outcome for patients undergoing LSF [ 5 ]. A cross-sectional study found that 83% of patients scheduled for LSF did not adhere to the World Health Organization recommendations regarding physical activity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study found that 83% of patients scheduled for LSF did not adhere to the World Health Organization recommendations regarding physical activity, i.e. 30 min per day [ 5 ]. Further, this seems to be unchanged 6 months after LSF [ 6 ], indicating that these patients may be at risk of poor health and lifestyle diseases due to insufficient physical activity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar degenerative disease (LDD) of the spine including disc herniation, spinal stenosis and other degenerative disc disease is fairly common among the people and also causes the considerable discomfort and dissatisfaction [1,2]. Most people of LDD are suffering from the low back pain (LBP) as an extremely common problem at some point in their life [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence to suggest that, to increase physical activity and function in this group of patients, post-surgical rehabilitation should start early, and the content of the rehabilitation should be based on a bio-psycho-social approach (5,(15)(16)(17). A systematic review by Greenwood et al found that "complex interventions", consisting of exercise and cognitive behavioural therapy, offer short-term and long-term functional bene ts for patients following LSF (18).…”
Section: Introductionmentioning
confidence: 99%